Prevention of varicose veins during pregnancy - Bakanauskaitė, Vitalija; Paulikienė, Simona (Slauga. Mokslas ir praktika, 2020)
This particular topic is relevant because one of the most common circulatory disorders are varicose veins and in accordance with the data of the Institute of hygiene in Lithuania in the year 2017, one of the main causes of death were diseases of the circulatory system [1]. Varicose veins for pregnant women can lead to pulmonary arterial thromboembolism which causes death to 12-15 percent of pregnant women [2].The article analyses the development of the varicoise veins prevention during pregnancy. Using a qualitative research method was found out what are the investigators opinion and actions to prevent the development of the varicose veins. Where was 10 investigators which hasn‘t got varicose veins and where first semester and first time pregnant.The investigation has shown that investigators follows the eating recommendations for pregnant womens, performs physical activities, uses compression therapy and uses lubricants for the feet. Because of a surrounding persons incentive, personal desire and knowledge of the importance of prevention investigators starts the prevention. If investigators are looking for information they obtain it from doctor, nurse, family members, the lectures for pregnant women and online source. Investigators does not do any varicose veins prevention if there are no personal desire, other persons incentive, knowledge and correct information about prevention.